UJI EFEKTIVITAS KOMBINASI JENIS PUPUK ORGANIK DAN BIOURIN KELINCI TERHADAP KEMANTAPAN AGREGAT DAN PERTUMBUHAN TEBU PADA FASE PERTUNASAN - Dewi Nur Istiqomah; Diaz Gustomo; Sugeng Prijono (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2015)
The success of sugar cane production is affected by the condition of the plant in the early phase (germination). The improvement of sugarcane growth can be done by improving soil physical properties using organic matter such as mature compost, blotong, and biourine of rabbit. The objective of this study was to explore the effects mature, blotong, and biourine of rabbit on soil aggregate stability and the early growth of the sugar cane (germination phase). The experiment was held in P3GI (Pusat Penelitian Perkebunan Gula Indonesia) in Pasuruan, Jawa Timur. The experiment used randomized block design with 8 treatments and 5 replications. The treatments were P0 control (without organic matter), P1 (blotong t ha-1), P2 (mature compost 20 t ha-1), P3 (biourine of rabbit 10 L ha-1), P4 (mature compost 20 t ha-1 + blotong t ha-1), P5 (biourine of rabbit 10 L ha-1 +blotong t ha-1), P6 (biourine of rabbit 10 L ha-1 +Â mature compost 20 t ha-1), P7 (biourine of rabbit 10 L ha-1 +Â mature compost 20 t ha-1 +blotong t ha-1). The results showed that the application of combination of mature compost, blotong, and biourine of rabbit affected soil aggregate stability. The highest value in 12 MST was in biourine 10 L ha-1 + mature compost 20 t ha-1 (P6) was 3.41 mm. Application of mature compost 20 t ha-1 + blotong t ha-1 (P4) gave highest plant height of Â 84.62 cm